1998
DOI: 10.1038/ng0398-231
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial transcription factor A is necessary for mtDNA maintance and embryogenesis in mice

Abstract: The regulation of mitochondrial DNA (mtDNA) expression is crucial for mitochondrial biogenesis during development and differentiation. We have disrupted the mouse gene for mitochondrial transcription factor A (Tfam; formerly known as m-mtTFA) by gene targetting of loxP-sites followed by cre-mediated excision in vivo. Heterozygous knockout mice exhibit reduced mtDNA copy number and respiratory chain deficiency in heart. Homozygous knockout embryos exhibit a severe mtDNA depletion with abolished oxidative phosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

54
1,125
2
6

Year Published

2000
2000
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 1,435 publications
(1,219 citation statements)
references
References 26 publications
54
1,125
2
6
Order By: Relevance
“…S3a,b) led to both mtDNA and mtRNA depletion, and a consequent deficiency in ETC function in the same manner as EtBr treatment (Fig. 4a–c), as described previously 20. In contrast to the pseudo‐ρ0 cells (Fig.…”
Section: Resultssupporting
confidence: 82%
“…S3a,b) led to both mtDNA and mtRNA depletion, and a consequent deficiency in ETC function in the same manner as EtBr treatment (Fig. 4a–c), as described previously 20. In contrast to the pseudo‐ρ0 cells (Fig.…”
Section: Resultssupporting
confidence: 82%
“…A high rate of mitochondrial transcription occurs during cleavage of early embryos to meet high-energy demands and may require the new synthesis and transport of nuclearly encoded mitochondrial respiratory chain components (Larsson et al, 1998). Previous studies established that PPRC1 co-activates NRF1 and NRF2 and regulates many genes encoding protein products involved in mitochondrial respiration (Vercauteren et al, 2006(Vercauteren et al, , 2008.…”
Section: Developmental Dynamicsmentioning
confidence: 99%
“…The embryonic lethality of pprc1-null mice in our study was not unexpected, because deficiency of some other key components of the transcription of mitochondrial transcription, such as NRF1, NRF2, and TFAM, also leads to a similar form of early embryonic lethality in mice. This may be due to decreased expression of genes that regulate mitochondrial biogenesis and function (Larsson et al, 1998;Huo and Scarpulla, 2001;Ristevski et al, 2004).…”
Section: Developmental Dynamicsmentioning
confidence: 99%
“…Studies of knockout mice clarified that TFAM is essential for mtDNA maintenance 9 and that increased transgenic expression of TFAM results in an increase in the number of mtDNA copies in vivo 10 . Confocal microscopy studies have found that TFAM is distributed in a punctuate pattern within the mitochondrial network, colocalizes with mtDNA and is present in every mitochondrial nucleoid 11 .…”
mentioning
confidence: 99%